#TITLE_ALTERNATIVE# - SUSANTO(M9901814); Pembimbing : Vincent F yu, HADI
Shelf space is an important resource for automotive retailers since a great quantity of products competes with the limited shelf space for display. Retailer cannot only increase their profit directly without considering product prices, display facing areas, display orientations, shelf-space locations, and cost by proper shelf space management. This research develops a model that considers several aforementioned factors, and captures three dimensional product packaging characteristics. Unlike existing shelf-space allocation models, this research sets out to deepen the cost factor including purchasing cost, ordering cost, holding cost, and display cost. Further, we also take into account how to determine the economic order quantity based on specific range orders to a supplier. This research proposes to extend the limited stream of research by systematically addressing the shelf-space allocation problem and exploring alternative solution technique such as meta-heuristic approaches, more specifically, the particle swarm optimization (PSO) method to solve the problem.